Parental Perceptions of the Effectiveness of Abdul Latif Syakur's Quranic Learning Method - Syawaldi Syawaldi; Zulfani Sesmiarni; Yudi Gucandra (STIT Ahlussunnah Bukittinggi, 2026)
Traditional Quranic learning methods rooted in local Islamic intellectual traditions remain widely practiced in Indonesia; however, empirical studies examining their effectiveness from the perspective of parents are still limited. This study investigates parents' perceptions of the effectiveness of the Quranic learning method inherited from Shaykh Abdul Latif Syakur, a prominent Minangkabau Muslim scholar, which continues to be transmitted through a sanad-based pedagogical tradition in Quranic learning institutions. Employing a descriptive quantitative approach, data were collected through a five-point Likert-scale questionnaire consisting of 14 items covering two dimensions: reading fluency and Quranic writing ability. A total of 56 parents of students were selected using purposive sampling. Data were analyzed using descriptive statistical techniques, including mean scores and frequency distributions. The findings reveal a highly positive perception of the method's effectiveness, with an overall mean score of 4.35 out of 5. The reading fluency dimension obtained a mean score of 4.34, while the Quranic writing dimension achieved a mean score of 4.36. Furthermore, 89.28% of respondents categorized the method as positive or very positive. These findings indicate that the Abdul Latif Syakur Quranic learning method is perceived as effective in facilitating students' mastery of Quranic reading and writing skills. This study contributes to the growing discourse on indigenous Islamic pedagogy by providing empirical evidence of the continuing relevance of local scholarly educational heritage in contemporary Quranic education and its potential integration into community-based Islamic learning models.